The impact of inter-unit variations on small field dosimetry correction factors, with application to the CyberKnife system. (22nd January 2019) - Francescon, P; Kilby, W; Satariano, N; Orlandi, C; Elshamndy, S
Abstract: Small field dosimetry correction factors are usually determined from calculations or measurements using one specific example of a treatment system. The sensitivity of the corrections to inter-unit variation is therefore not evaluated. We propose two methods for this evaluation that could be applied to any system. We use them to assess the variability in for the CyberKnife System caused by design changes between pre-M6 and M6 versions, and to the variability in and resulting from measured beam-data variations across 139 units. We also perform measurements to investigate the differences in reported for microchambers in a CyberKnife-specific study versus TRS-483. The results show that is smaller for the M6 version than pre-M6 versions by 0.4% for a Farmer chamber, and 0.1% for shorter chambers. The presence or absence of a lead filter within the treatment head had no significant impact on . The beam-data analysis showed inter-unit variations in of ±0.8% (2 s.d.) for Farmer chambers and ⩽ ±0.5% for shorter cavities (<10 mm) pre-M6, reducing to 0.4% and 0.2% respectively with M6. Inter-unit variations for microDiamond and microchambers were ⩽ ±1% at 5 mm field size, except for microchambers with axis perpendicular to the beam where this was > ±2%. Differences of up to 9% were confirmed between Output Factors measured using a microchamber and corrected using TRS-483, and a consensus dataset for the same treatment unit determined using multiple detectors and Monte Carlo simulation. A set of practical recommendations for small field dosimetry with the CyberKnife System is derived from these results.